Fleet Management Cooperative Systems for Commercial Vehicles. (2016) - Surugiu, Maria Claudia; Stancel, Ion Nicolae
Abstract: This paper addresses the development of a system that facilitates the formation of a road train by informing in real-time the drivers of commercial vehicles, especially trucks with cargo, with information about position-related data, the speed of a road train and the necessary conditions to become part of such a train. By collecting information from fleets of trucks, the communication interface between the vehicle and the fleet monitoring server will be extended. The server will receive data from the vehicles and after a specific processing stage, a extended map will be generated with real-time information collected from the cars in traffic. The optimal route generation algorithm will be also extended, by using data received in real time. The data collected by the fleet monitoring server will be provided through a communication protocol to the ITS traffic server.